2016
DOI: 10.1177/0972150916645692
|View full text |Cite
|
Sign up to set email alerts
|

Critical Factors of Cloud Computing Adoption in Organizations: An Empirical Study

Abstract: Using extended Technology Acceptance Model (TAM), this study attempts to assess empirically crucial factors affecting cloud computing adoption intentions. It explores security, availability and compliance-related challenges in cloud computing and makes the necessary recommendation which can help to mitigate the risk in cloud computing. A framework was developed to test the effect of security, availability of cloud service provider and compliance-related factors on cloud computing adoption intentions mediated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 35 publications
2
31
0
8
Order By: Relevance
“…This damage directly lowers the consumer's willingness to pay. This is in line with the findings of Gangwar and Date () who show that security issues decrease the usefulness of cloud computing services for its customers.…”
Section: Model Set‐upsupporting
confidence: 92%
See 1 more Smart Citation
“…This damage directly lowers the consumer's willingness to pay. This is in line with the findings of Gangwar and Date () who show that security issues decrease the usefulness of cloud computing services for its customers.…”
Section: Model Set‐upsupporting
confidence: 92%
“…These risks cause many businesses to reassess carefully, whether to use the service at all (Mujinga & Chipangura, ). Furthermore, potential advantages may also be seen as disadvantages, as “the data placed is easy to locate [and] to send across the communication channels of different countries” (Gangwar & Date, , 889).…”
Section: Introductionmentioning
confidence: 99%
“…Various models have been proposed specifically to explain the adoption of technology, such as the technology acceptance model (TAM) (Davis, 1989), the unified theory of acceptance and use of technology (UTAUT) (Venkatesh, Morris, Davis, & Davis, 2003) and the technology organization environment (TOE) framework (Tornatzky, Fleischer, & Chakrabarti, 1990). Gangwar and Date (2016) used extended TAM model to find critical factors of CC adoption. The findings revealed that threat, risk, vulnerability, availability and support, and compliance are important determinants in Indian organizations.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The organizations are less likely to use any technology if they find it difficult to understand and integrate with their organizational processes (Premkumar and Roberts 1999;Verma and Bhattacharyya 2017). Complexity is a factor that was found to have a negative influence on the adoption of cloud computing in India (Gangwar and Date 2016;Narwane et al 2019a, b).…”
Section: Referencesmentioning
confidence: 99%